THE INFLUENCE OF WORK MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES IN THE OFFICE KARANG BAHAGIA SUBDISTRICT, BEKASI - Riski Eko Ardianto (Jurnal Ekonomi, 2022)
The right human reseource are a very important requirement to creat a competitive advantage for a company. The succes or failure of a company cannot be separated from the performance of employees. There are several factors that affect employee performance, one of which is. Work Motivation and Work Discpline. This study aims to determine whether ther is an effect of work motivation and discipline on employee performance at the Karang Bahagia sub-district office, kab. Bekasi. The data collection of this research used observation and questionnaires which were distributed to 37 employees at the happy sub-district office. This study uses a nonprobability sampling technique, this research is a quantitative study with the statistical assistance program SPSS version 28, the analytical method used is multiple Linear Regression to prove the hypothesis of this study has met the validity test, realiability test, calcic assumption test and then processesd to get regression equality. Based on the result of the discussion in this study, it can be ascertained that work motivation has a possitive and significant effect on employee performance, discipline has a positive and significant effect on employee performance, and there is a positive and significant influence on employee work discipline.